2020
DOI: 10.16970/entoted.680696
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the Anatolian endemic tiger beetle, Cephalota circumdata cappadocica Franzen, 1996 (Coleoptera: Carabidae: Cicindelinae): a study showing the effectiveness of geometric morphometrics

Abstract: Sexual dimorphism in the Anatolian endemic tiger beetle, Cephalota circumdata ssp. cappadocica Franzen, 1996 (Coleoptera: Carabidae: Cicindelinae):a study showing the effectiveness of geometric morphometrics 1Anadolu endemik kaplan böceği, Cephalota circumdata ssp. cappadocica Franzen, 1996 (Coleoptera: Carabidae: Cicindelinae)'de eşeysel dimorfizm: geometrik morfometrinin etkinliğini gösteren bir çalışma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Prior to our study, interspecific and intersexual body shape variations were observed only in a single tiger beetle species but not yet quantified for any Lophyra species nor for any North African Cicindelidae. Moreover, this study is the first attempt to statistically examine morphological variation in North African desert tiger beetles and one of the only few in this beetle family in general (e.g., Doğan Sarikaya et al, 2020; Espinoza‐Donoso et al, 2020; Franzen, 2007; Jaskuła, 2005; Pearson & Vogler, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to our study, interspecific and intersexual body shape variations were observed only in a single tiger beetle species but not yet quantified for any Lophyra species nor for any North African Cicindelidae. Moreover, this study is the first attempt to statistically examine morphological variation in North African desert tiger beetles and one of the only few in this beetle family in general (e.g., Doğan Sarikaya et al, 2020; Espinoza‐Donoso et al, 2020; Franzen, 2007; Jaskuła, 2005; Pearson & Vogler, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is known that females are larger and wider than males (Espinoza‐Donoso et al, 2020; Jaskuła, 2005; Pearson & Vogler, 2001); in some genera different size and shape of labrum and mandibles between sexes was found too (Cassola & Bouyer, 2007; Jones & Conner, 2018; Kritsky & Simon, 1995). Doğan Sarikaya et al (2020) noted differences in shape and size of head and pronotum between males and females of tiger beetles. Rarely, sexual differences can be observed also in the coloration of the body (Kippenhan, 1997; Pearson & Vogler, 2001) or only some parts of body are differently colored, for example, prothoracic tarsal pads (Palmer, 1981) or mandibles (Cassola & Bouyer, 2007; Pearson, 1988), which in the case of males are usually white, while in females they are darkly colored.…”
Section: Introductionmentioning
confidence: 99%
“…Most entomologists still consider these insects within their family. However, in some recent publications, tiger beetles are evaluated in Cicindelinae subfamily of Carabidae family (Jaskuła and Rewicz, 2015;Serrano and Capela, 2013;Young, 2015;Matalin and Chikatunov, 2016;Dogan Sarikaya et al, 2020). Nevertheless, this view has not been acknowledged yet by many researchers around the world, and it is claimed that, based on the distinct differences especially in their morphological structures, they need to be considered as separate families.…”
Section: Introductionmentioning
confidence: 99%